Support measures for adolescents’ school anxiety mitigation - Orska, Rita (Social Welfare: Interdisciplinary Approach, 2017)
School anxiety is one of the situational anxiety types. The feeling of anxiety in school is unavoidable, yet the intensity of this feeling should not exceed each student’s individual “critical point”, as exceeding causes disorientation instead of mobilisation. School anxiety can be expressed in behaviour in the most various forms: from passivity in classes, unsure answers, to “super-diligence”, a wish to do everything perfectly. It is necessary to help students find effective techniques to regulate anxiety, overcome diffidence and other expressions of emotional imbalance. A set of preventive measures must be established, which will help students develop necessary skills for anxiety mitigation and gain successful anxiety overcoming experience. Educational measures regarding this issue are necessary for teachers and parents as well.